Data Analytics Usage for Improvements in African Startups - Amama, Ushang Desmond; Sládek, Pavel; Maryška, Miloš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
African startups operate in a dynamic yet challenging environment characterised by resource constraints, infrastructural deficits, and fragmented markets, contributing to a five-year survival rate below 50%. This study investigates the transformative potential of data analytics in mitigating these barriers, with a focus on accelerating product development, enhancing decision-making, and improving operational efficiency. Employing a mixed-methods approach, the research integrates qualitative insights from structured interviews with founders, CEOs, CTOs, and data scientists across Nigerian and Czech startups, alongside quantitative analysis of secondary data from Tracxn. Statistical techniques, including logistic regression, were applied to a dataset of 2,403 startups to identify correlations between data analytics adoption and key success metrics, such as reduced time-to-market and increased funding efficiency. A comparative analysis of African, Czech, and U.S. ecosystems revealed critical gaps in Africa’s startup landscape, including limited access to venture capital, underdeveloped academic-industry collaborations, and infrastructural inefficiencies. However, case studies of firms like Nigeria’s Moniepoint (FinTech), Czechia’s Rohlik (e-commerce), and OpenAI (AI) demonstrated how data-driven strategies—such as predictive analytics, customer behaviour modeling, and real-time supply chain optimisation—can overcome these challenges. For instance, Moniepoint’s integration of Google Cloud analytics tools reduced transaction processing times by 30%, while Rohlik’s AI-driven logistics improved delivery accuracy by 25%. The study culminates in a practical framework for African startups, emphasising scalable analytics adoption, ethical data practices, and cross-sector partnerships.
Key components include modular analytics tools for resource-constrained environments, strategies to bridge talent gaps through localised training programs, and metrics for tracking innovation cycles. By establishing a clear link between data analytics adoption and startup survival, the framework offers actionable pathways for startups to thrive. These findings contribute to academic discourse on innovation ecosystems while providing policymakers and entrepreneurs with evidence-based strategies to foster sustainable growth, positioning data analytics as a catalyst for Africa’s economic transformation.
Vedoucí práce: Pavel Sládek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data and business [obor dipl. práce]; diplomové práce; master's theses